Detrital zircons in basement metasedimentary protoliths unveil the origins of southern India - Plavsa, Diana; Collins, A.; Payne, J.; Foden, J.; Clark, Christopher; Santosh, M. (Geological Society of America, 2014)
Coupled U-Pb and Hf isotopic analysis of detrital zircons from metasedimentary rocks of the Southern Granulite terrane (India) provides provenance information that helps unravel their paleotectonic position before Gondwana amalgamated. The metasedimentary packages of the Salem block (southernmost extension of Dharwar craton) record a restricted juvenile late Archean to early Paleoproterozoic (2.7–2.45 Ga) source provenance and epsilon Hf values between +0.3 and +8.8. Similar late Archean juvenile crust is found throughout the Dharwar craton and represents a likely source for the Salem block metasedimentary rocks. By contrast, the metasedimentary rocks of the Madurai block (south of the Salem block) show a predominantly Archean to Paleoproterozoic provenance (3.2–1.7 Ga) in the northern part of the Madurai block and a largely late Mesoproterozoic to Neoproterozoic provenance (1.1–0.65 Ga) in the southern part of the Madurai block. Collectively, the Madurai block metasedimentary rocks record a mixture of reworked Archean and Paleoproterozoic sources, as well as juvenile Paleoproterozoic, late Mesoproterozoic, and evolved Neoproterozoic sources. These detrital signatures best fit the combined basement ages of the Congo-Tanzania-Bangweulu block and central Madagascar (Azania), thus linking the tectonic evolution of the southernmost tip of India to these domains throughout much of the Proterozoic. The diachroneity of metamorphic ages obtained from the rims of Madurai block detrital zircons attests to their poly-metamorphic history that is different from that of the Salem block. The contrasting metamorphic and depositional histories between the Salem and Madurai blocks place them on opposite sides of the Mozambique Ocean until the latest Neoproterozoic when they came together to form Gondwana.